(untitled) (Dhaka University Law Journal, 2025)
Both public policy and legal policy warrant that justice is delivered to the litigant people without any excuse. The power to do ‘complete justice’ avails the Supreme Court a vast residual power to complete the arc of justice by overcoming hurdles and roadblocks barring it from meeting the end of justice. The power is marked as an inherent and extraordinary discretionary power – not like other statutory discretionary powers – by virtue of which the Supreme Court can issue any decree or order for the end of complete justice subject to a few limitations. Article 104 of the Constitution of Bangladesh and Article 142 of the Indian Constitution empower the Appellate Division of the Supreme Court of Bangladesh and the Supreme Court of India respectively to exercise this power. Though the power is of wide amplitude being vested upon the apex court of the country by the constitution itself, it is nonetheless residual in nature. The contours of the power of ‘complete justice’ has remained a contentious issue in India—some arguing that the power can be exercised only restrictively, while others argue that the scope of the power is expansive. In absence of clear yardsticks to decide which situations entail the necessity of exercising the power, the power is still an enigma to the legal academia, though the Supreme Court of India seems to prefer liberal interpretation of the power. So, its ambit is wide and elastic enough to cover any new situation of necessity. Bangladesh Supreme Court has also exercised this power for a long time now, but no academic analysis of its journey has been undertaken so far. This article aims to elucidate the philosophy of devising the power and also to outline its scope and the trends of judicial interpretations in Bangladesh and India through a comparative analysis. Dhaka University Law Journal, Vol. 35 (1), 2024 P. 1-30